LOW-COST MODULAR BATTERY MONITORING SYSTEM FOR SMALL SCALE TESTING - Hanapiah, Hairulhaziq; Toha, Siti Fauziah; Malik, Hafizi; Idris, Ahmad Syahrin (PERINTIS eJournal, 2022)
Electric vehicles have become a notable topic in recent years, and they are powered by a rechargeable lithium polymer (LiPo) battery. This paper describes a battery monitoring system that uses LiPo as the test subject to monitor its stability in the event of further improvement and safety limitations. A number of battery monitoring systems have been developed, but only a few are small and comprehensive. The proposed battery monitoring system will monitor the LiPo battery's state of charge (SoC), state of health (SoH), charge, and discharge using a user-friendly and affordable method. First, the data of the LiPo battery's discharge curve of voltage is collected using a voltage sensor connected in parallel with a closed loop circuit consisting of a LiPo battery and a DC motor connected in series. Second, the SoC is calculated based on the average total time spent before the voltage drop. Several trials are conducted to examine the consistency in monitoring the charge of allocated LiPo batteries. As a result of this study, a low-cost prototype for battery monitoring was developed, which proved to be reliable and perform well with a small margin of error.